E-Cul-Tours (Gruppo editoriale Tab Srl, 2024)
The publication presents and critically discusses cases of cultural heritage management in the perspective of the valorization of cultural heritage in the tourism context. The authors reflect on how cultural heritage might be used in a sustainable way within the tourism experience: while various tourism service providers claim cultural heritage as commodity to be used in tourism, this contribution aims at a more adequate utilization, by enriching the perspective through consumers, providers and local communities involvement.